2022
DOI: 10.24272/j.issn.2095-8137.2021.426
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NDM-5-producing <i>Enterobacteriaceae</i> isolates from retail grass carp (<i>Ctenopharyngodon idella</i>) and evidence of <i>bla</i><sub>NDM-5</sub>-bearing IncHI2 plasmid transfer between ducks and fish

Abstract: We aimed to characterize NDM-5-producing Enterobacteriaceae from aquatic products in Guangzhou, China. A total of 196 intestinal samples of grass carp collected in 2019 were screened for carbapenemase genes. Characterization of bla NDM-5 positive isolates and plasmids was determined by antimicrobial susceptibility testing, conjugation experiments, Illumina HiSeq, and Nanopore sequencing. One Citrobacter freundii and six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
3
7
0
Order By: Relevance
“…Since its first report in British, bla NDM-5 has been detected in clinical isolates from Europe, Asia, South America, the United States of America and Australia (Nakano et al, 2014;Wailan et al, 2015;Baek et al, 2019;López-Hernández et al, 2020;Ramadan et al, 2020;Costa et al, 2021). Notably, the prevalence of bla NDM-5 isolates from food-producing animals has been sporadic in aboard (Ghatak et al, 2013), although there are more relevant reports in China (Yang et al, 2016;Kong et al, 2017a;Yao et al, 2020;Zhao et al, 2021;Lv et al, 2022). In the current study, our results revealed a wide contamination of NDM-positive Enterobacteriaceae in ten different provinces.…”
Section: Discussionsupporting
confidence: 46%
“…Since its first report in British, bla NDM-5 has been detected in clinical isolates from Europe, Asia, South America, the United States of America and Australia (Nakano et al, 2014;Wailan et al, 2015;Baek et al, 2019;López-Hernández et al, 2020;Ramadan et al, 2020;Costa et al, 2021). Notably, the prevalence of bla NDM-5 isolates from food-producing animals has been sporadic in aboard (Ghatak et al, 2013), although there are more relevant reports in China (Yang et al, 2016;Kong et al, 2017a;Yao et al, 2020;Zhao et al, 2021;Lv et al, 2022). In the current study, our results revealed a wide contamination of NDM-positive Enterobacteriaceae in ten different provinces.…”
Section: Discussionsupporting
confidence: 46%
“…The bla NDM-5 and bla CTX-M-15 genes were co-carried on an additional large-size IncFIB/IncHI2 plasmid (360,100 bp) also displaying the armA , aph(3′)-VI , aac(6′)-Ib , aadA1 , qnrS1 , sul1 , sul2 and dfrA5 genes. Such hybrid plasmids have already been reported to carry different resistance genes such as mcr-1 or bla NDM-5 [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Duck–fish polyculture is a common circular farming model in the Pearl River Delta in southern China, specifically in Guangdong Province. In this model, duck manure is discharged directly without treatment, and a large number of ARGs or residual agents can directly contaminate fish ponds, promoting the transmission of ARGs between ducks and fish [ 14 , 23 , 24 ]. Previous studies have shown that fish–duck integrated farming systems have become a hotspot environment for the occurrence and proliferation of ARGs and ARB, and both ARGs and pathogen-related ARB have been detected in the water and sediment of this culture system [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%